After the U.S hegemonic retreat : Russia's foreing and security policy in the middle east - González Levaggi, Ariel (2018)
Fil: González Levaggi, Ariel. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales. Departamento de Ciencias Políticas y Relaciones Internacionales; Argentina